A Correlational Study: Listening and Reading Anxiety of Turkish Children During the Covid-19 Pandemic - Deniz Melanlıoğlu; Mehmet Katrancı (Foxton Books, 2022)
As the source of an individual's learning, listening and reading skills are also a prior condition to use speaking and writing skills. Therefore, eliminating the problems encountered in these skills is also important for the development of other skills. In this study, the aim is to determine the listening and reading anxiety levels of students and the relationship between them in terms of various variables during the Covid-19 pandemic which has been emphasized in various studies to cause learning losses. In accordance with the stated aim, the target population of the research consists of secondary school students. Data from the participants were collected with the use of the Listening Anxiety Scale for Secondary School Students and the Reading Anxiety Scale, and the SPSS program was used to analyze the data. As a result, it was determined that listening anxiety levels of the participants were moderate and reading anxiety levels were low, and there was a positive and significant relationship between the listening and reading anxiety levels of secondary school students.